Liminal legality and delayed citizenship: The identity crisis of Indonesian migrant children in Sabah and Sarawak - Arpannudin, Iqbal; Dewantara, Jagad Aditya (Universitas Negeri Yogyakarta, 2025)
This article explores statelessness as a multidimensional problem that directly impacts access to education and civic identity, particularly in Asia and Europe. Around 10 million people worldwide are stateless, deprived of basic rights such as education, health and employment due to the absence of legal documents. In Malaysia, thousands of children from migrant communities and ethnic minorities such as the Rohingya and Filipinos in Sabah lack access to national schools and public services due to their legal status. Meanwhile, in Europe, historical legacies such as the breakup of the Soviet Union and structural discrimination mean that many children from groups such as the Roma are born stateless and excluded from the education system. This article highlights that formal policies, such as